The Naming of Schools in Bangkok: Case Study Origin of Name - Chunpuang, Thunchanok; Jaitheang, Natnicha; Pathomsitthipanit, Nidjakun; Poljaidee, Intuon; Losakul, Salocha; Katakool, Patcharapan (วารสารมนุษยศาสตร์ มหาวิทยาลัยมหามกุฏราชวิทยาลัย; Vol 11 No 1 (2019): วารสารมนุษยศาสตร์ มหาวิทยาลัยมหามกุฏราชวิทยาลัย, 2019)
This researching aims at studying in the names of the school in Bangkok. Byanalyzing the list of the name of public schools under the Office of the Basic Education Commission, Department of Education Bangkok Metropolitan Administration, and the list of the name of private schools under the Department of General Education. Selected by Extra-large, Large, and Middle school (Classified by number of students). Appears a list of schools that can analyze a list of 446 names. The result of the study indicated that the origin of the name of the school comes from the name 1 type. The most common is named by the school’s location, or school environment, or what is available thing in the school. The second is named by important people. The Third is named by the purpose, respectively. In addition, find the origin of the name of the school comes from the name 2 types. The most common is named by the school’s location, or school environment, or what is available thing in the school and named by important people. The second is named by important event and named by the school’s location, or school environment, or what is available thing in the school. The Third is named by the school’s location, or school environment, or what is available thing in the school and named by the purpose. And is named by the school’s location, or school environment, or what is available thing in the school and named by the agency, company and organization, respectively.